If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(x + -6) = 2(x + -9) Reorder the terms: 15(-6 + x) = 2(x + -9) (-6 * 15 + x * 15) = 2(x + -9) (-90 + 15x) = 2(x + -9) Reorder the terms: -90 + 15x = 2(-9 + x) -90 + 15x = (-9 * 2 + x * 2) -90 + 15x = (-18 + 2x) Solving -90 + 15x = -18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -90 + 15x + -2x = -18 + 2x + -2x Combine like terms: 15x + -2x = 13x -90 + 13x = -18 + 2x + -2x Combine like terms: 2x + -2x = 0 -90 + 13x = -18 + 0 -90 + 13x = -18 Add '90' to each side of the equation. -90 + 90 + 13x = -18 + 90 Combine like terms: -90 + 90 = 0 0 + 13x = -18 + 90 13x = -18 + 90 Combine like terms: -18 + 90 = 72 13x = 72 Divide each side by '13'. x = 5.538461538 Simplifying x = 5.538461538
| g^2-17g+60=0 | | (2y-3)dx+(2x+3y^2)dy=0 | | 4x*cos(x)=0 | | 6n+9+12=3 | | 9n+8+14=8 | | 0=-16t^2+192t+30 | | 6n+2+12=5 | | Cos^2b+2senb+2=0 | | 6x=55/2 | | x+10??2=2x | | 68+x=x | | -(2/5)t=1/7 | | (-2/5)t=1/7 | | 3sin(5x)=1 | | x+2x+x+30=102 | | 2(x+5)=-1 | | X+4=-47 | | -7a+5+8a=5-23 | | 5-2x=-4x-2 | | 48/1-9/5= | | -3+2(-2)=1+4(-2) | | -3y=-6x+9 | | (x-1)^(2/3)=64 | | X+3=-71 | | 4x^(9/2)-20=0 | | 60x-y-80=0 | | 60x+y+80=0 | | 5cos(x)+5sin(x)=5 | | 6h+73=46 | | 4ln(20/0) | | 13z-1=14z-6 | | 4a+2b=39 |